EFFECT OF INCREESE AND DECREASE OF PROPOLIS GATHERING ON THE EUROPEAN FOULBROOD FOR SOME OF HONEY BEES RACES - Salim Jameel Jarjees (Mesopotamia Journal of Agriculture)
The relation of increase or decrease gathering of propolis on infection with European Foulbrood when studying three races of honey bees that varied in their behavior of gathering propolis for five periods showed to be higher in the colonies of the Criniolian race, followed by the Italian and local Iraqi race 113.9 , 95.5 and 45.8 mm2/colony, respectively. According to Duncan's' multiple range test at (p=0.05). The study also showed that the highest increase of infected area associated with European Foulbrood was in June,with an average of (132.3 mm2/colony) with the lowest was in March, averaging (11.0 mm2 /colony) for the three different races.The local Iraqi race gathered the highest quantities of propolis, followed by the Italian race, and the Criniolian race 3.1 , 1.6 and 1.3 gr./ frame, respectively. The results showted that the highest quantities of propolis was gathered in June with an average of (2.8 gr./ frame) and the lowest quantities were gathered in March with an average of (1.1 gr. / frame ).